Association between interpregnancy interval and maternal and neonatal adverse outcomes in women with a cesarean delivery: a population-based study - Hong Dong; Jinghan Chi; Wei Wang; Lei Liu (BMC, 2023)
Abstract Background Interpregnancy interval (IPI) has been linked with several maternal and neonatal adverse events in the general population. However, the association between IPI and maternal and neonatal outcomes in women whose first delivery was by cesarean delivery is unclear. We aimed to investigate the association between IPI after cesarean delivery and the risk of maternal and neonatal adverse events. Methods Women (aged ≥ 18 years) whose first delivery was cesarean delivery with 2 consecutive singleton pregnancies from the National Vital Statistics System (NVSS) database between 2017 and 2019 were included in this retrospective cohort study. In this post-hoc analysis, logistic regression analyses were used to examine IPI (≤ 11, 12-17, 18-23 [reference], 24-35, 36-59, and ≥ 60 months) in relation to the risk of repeat cesarean delivery, maternal adverse events (maternal transfusion, ruptured uterus, unplanned hysterectomy, and admission to an intensive care unit), and neonatal adverse events (low birthweight, premature birth, Apgar score at 5 min < 7, and abnormal conditions of the newborn). Stratified analysis based on age (< 35 and ≥ 35 years) and previous preterm birth. Results We included 792,094 maternities, 704,244 (88.91%) of which underwent a repeat cesarean delivery, 5,246 (0.66%) women had adverse events, and 144,423 (18.23%) neonates had adverse events. After adjusting for confounders, compared to an IPI of 18-23 months, the IPI of ≤ 11 months [odds ratio (OR) = 1.55, 95% confidence interval (CI): 1.44-1.66], 12-17 months (OR = 1.38, 95%CI: 1.33-1.43), 36-59 months (OR = 1.12, 95%CI: 1.10-1.15), and ≥ 60 months (OR = 1.19, 95%CI: 1.16-1.22) were associated with an increased risk of repeat cesarean delivery. In terms of maternal adverse events, only IPI of ≥ 60 months (OR = 0.85, 95%CI: 0.76-0.95) was observed to be associated with decreased risk of maternal adverse events in women aged < 35 years. In analysis of neonatal adverse events, IPI of ≤ 11 months (OR = 1.14, 95%CI: 1.07-1.21), 12-17 months (OR = 1.07, 95%CI: 1.03-1.10), and ≥ 60 months (OR = 1.05, 95%CI: 1.02-1.08) were related to an increased risk of neonatal adverse events. Conclusion Both short and long IPI were associated with an increased risk of repeat cesarean delivery and neonatal adverse events, and women < 35 years may benefit from a longer IPI.